FORMATION OF TEACHER’S SOCIO-ECONOMIC COMPETENCE THROUGH HIGH SCHOOL’S PUBLIC MANAGEMENT - Inna G . Ryabova (National Research Mordova State University, 2016)
Introduction: the article explores one of topical issues in modernisation of contemporary education – enhancement of socio-economic competence of a teacher. Social and economic functions, such as goal-setting, planning, organisation, analysis, control and correction act as integral components in its structure.